Identification of Endophyte Fungi in Bali Grape Vine (Vitis vinifera L. Var Alphonso lavalle) and its Potential Antagonists Against Botrytis cinerea Pers. cause of Grey Rot Disease - Utama, Putu Anggan Pradipta; Wahyuni, Meitini Proborini; Parwanayoni, Ni Made Susun (Metamorfosa: Journal of Biological Sciences, 2021)
This research aims to isolate and test the ability of endophytic fungi from the Bali Grape plant ( Vitis vinifera L. var Alphonso lavalle ) against botrytis cinerea pers. cause of gray rot in Grapes Bali. This research is an exploration study that is then continued with experimental. This research sample was isolated from Balinese grapes, namely healthy roots, stems, and leaves as well as diseased fruit parts from Balinese vineyards in Banyupoh Village, Gerokgak, Buleleng, Bali. Isolates of endophyte fungi that are successfully isolated are then tested using dual culture methods against pathogenic fungi. The test results of five isolates of endophytic fungi obtained three types of fungi that have the tasteless power of two types of fungi Trichoderma spp. (1) (2) and Mucor spp. with consecutive bonding power of 90.67 ± 16.17%, 75.67 ± 31.13%, and 82.67 ± 39.02. These results show that endophyte fungi have potential as biocontrol agents. Keywords : Mushroom endophyte, Botrytis cinerea Pers. , Biocontrol